Innovation in International Business (European Journal of Multidisciplinary Studies, 2017)
Nowadays, international business has a relevant role in the global economy. This is due to the connection that international business has with globalization. Also, innovation has a key role in the development of international business. Innovation is considered like the basic dynamic of today economy development. The role of innovation can be evaluated, by other stakeholders who operate in the same market, as an important factor of increasing the company’s value. A country that is interested to has his own innovation in order to develop his national economy, has to establish research and development centres, research institutes , universities, etc. Globalization development is associated with the development of basic rights for the protection and the development of "global products’. Different countries vary in the extent to which they protect intellectual property and enforce intellectual property regulations. The presence of strong, enforceable, consistent property rights serves to make the world flatter. However, as long as significant differences in property rights exist around the globe, the world will be far from flat with respect to innovation.In this paper, we will focus in intellectual property. We will explain what the intellectual property is, and what are the types of intellectual property. Further, we will see the differences in legislation that different countries have in the protection of intellectual property. At the end of this paper we will focus at the innovation of the business in Europe and in Albania.